THE EFFECT OF SCHOOL HEAD LEADERSHIP ON PROFESSIONAL COMPETENCY OF BASIC SCHOOL TEACHERS - Halimatussakdiah Halimatussakdiah (JURNAL HANDAYANI PGSD FIP UNIMED, 2019)
Abstract: The purpose of this study was to determine the effect of principals' leadership on the professional competence of elementary school teachers. The type of research conducted was ex post facto with quantitative analysis. Data analysis using descriptive correlational techniques and analysis requirements with normality test and linearity test. Sedangkan uji hipotesis dengan korelasi product moment. The results of the study indicate that there is a strong relationship between the leadership of the principal and the professional competence of primary school teachers. While the R2 value of 0.536 explains that the principal's leadership will have an effect of 53.6% on the professional competence of elementary school teachers. Hypothesis test results obtained tcount of 6.175 > 1.694 which means Ha is accepted. Keywords: Leadership, School. Abstrak: Tujuan penelitian ini adalah untuk mengetahui pengaruh kepemimpinan kepala sekolah terhadap kompetensi profesional guru sekolah dasar. Jenis penelitian yang dilakukan adalah  ex post facto dengan analisis kuantitatif. Analisis data menggunakan teknik deskriptif korelasional dan persyaratan analisis dengan uji normalitas dan uji linieritas . Sedangkan uji hipotesis dengan korelasi product moment. Hasil penelitian menunjukkan bahwa ada hubungan yang kuat antara kepemimpinan kepala sekolah dengan kompetensi profesional guru sekolah dasar Sedangkan nilai R2 sebesar 0,536 menjelaskan bahwa kepemimpinan kepala sekolah akan memberikan pengaruh sebesar 53,6% terhadap kompetensi profesional guru Sekolah Dasar. Hasil uji hipotesis diperoleh nilai thitung  sebesar 6,175 > 1,694 yang berarti Ha diterima. Kata Kunci: Kepemimpinan, Sekolah